The Barons' Crusade : A Call to Arms and Its Consequences - Lower, Michael (Book collections on Project MUSE., 2005)
This first full-length treatment of the Barons' Crusade examines the call for holy war and its consequences in Hungary, France, England, Constantinople, and the Holy Land.